Sequences implicated in the processing of Thermus thermophilus HB8 23S rRNA. - Hartmann, R K (1987)
Nuclease S1 mapping analyses were performed in order to detect processing intermediates of pre-23S rRNA from Thermus thermophilus HB8. Two processing sites were identified downstream the start of transcription and several consecutive cleavage sites are associated with the mature 5'-end. In the 3'-flanking region one "primary" site and two cleavages which generate short-living intermediates were detected. A series of successive intermediates in the region of the mature 3'-end implies the existence of--in analogy to Escherichia coli--a 3'-exonucleolytic activity. The data were correlated with potential secondary structures within the pre-23S rRNA, which exhibit various repeated sequence elements. M13 sequencing data support the existence of one secondary structural element associated with the strong "primary" cleavage site in the 3'-flanking region. In T. thermophilus we can exclude the formation of an extended base-paired and precursor-specific stem enclosing the 23S rRNA which is inferred to mediate recognition by RNase III in E. coli.